Analysis of the Quality of Final Semester Assessment (PAS) Questions for Al-Qur'an Hadith Class VIII MTS - Indah Rahmawati; Dina Hermina (Kasyafa: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the quality of the items in the Final Semester Examination (Penilaian Akhir Semester/PAS) of Qur’an Hadith for Grade VIII MTs in terms of item validity, reliability, difficulty level, discrimination index, and distractor effectiveness. This research employed a quantitative descriptive approach. The instrument analyzed consisted of 40 multiple-choice items with 21 student respondents. Data analysis was conducted using item analysis techniques supported by Microsoft Excel. The results show that 25 items were classified as valid, while 15 items were invalid. The instrument reliability was categorized as very high, with a KR-20 coefficient of 0.932. Most items were in the moderate difficulty category (85%), and the discrimination index was predominantly in the good to very good category. In addition, distractor effectiveness analysis indicated that most distractors functioned properly, and no items were found in which all distractors were non-functional. Overall, the instrument demonstrates fairly good quality, although several items still require revision. Furthermore, 14 items met all quality criteria and can serve as references for future assessments.